The mathematics and physics of body surfing - de Mestre, N. (International Journal of Computer Science in Sport, 2004)
Waves on the ocean are generated well away from any shoreline and travel under a prevailing wind towards a distant shore. These deep-water waves eventually become shallow-water waves and break near the shore creating a turbulent surf front of bubbles, foam and spray, encompassing secondary breaking and smaller splashing waves. Human surfers can propel themselves shorewards on these breakers or broken waves; the skill being termed body surfing.